2022
DOI: 10.1002/jlb.3ma1221-489r
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of heparin-binding protein as an acute-phase inflammatory marker in interstitial lung disease

Abstract: The role of heparin‐binding protein (HBP) as an acute inflammatory marker in acute exacerbations of interstitial lung disease (AE‐ILD) and some stable ILD patients is not well‐established. The significance of increasing HBP during an AE‐ILD is examined and the first attempt to incorporate HBP into the ILD evaluation system is made. Then, the benefit of HBP in AE‐ILD was investigated. ILD patients (n = 108) were divided into subgroups based on the phase and severity of the disease. Linear trends of HBP across s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 72 publications
(168 reference statements)
0
7
0
Order By: Relevance
“… 25 A previous study has demonstrated the predictive value of HBP for acute exacerbations of interstitial lung disease. 26 The mechanistic pathways were probably similar to pulmonary injury in CAP.…”
Section: Discussionmentioning
confidence: 96%
“… 25 A previous study has demonstrated the predictive value of HBP for acute exacerbations of interstitial lung disease. 26 The mechanistic pathways were probably similar to pulmonary injury in CAP.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with acute infection have significantly higher levels of HBP, when compared to patients with a stable disease. Furthermore, HBP has been shown to have higher accuracy, when compared to CRP and PCT, in detecting pulmonary infections in ILD [ 10 ] For patients with COVID-19 infection, HBP is significantly elevated, but this level is negatively correlated with oxygen saturation, creatinine and lactate levels. Moreover, it was reported that HBP is an independent risk factor for death within 28 days [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HBP can directly kill both Gram-positive and Gram-negative bacteria, and further enhance bacterial clearance by attracting macrophages, lymphocytes, and even more neutrophils to the site of infection [ 8 ]. Hence, HBP was suggested as a novel and valuable biomarker for sepsis and interstitial lung disease complicated by infection [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with acute infection have signi cantly higher levels of HBP, when compared to patients with a stable disease. Furthermore, HBP has been shown to have higher accuracy, when compared to CRP and PCT, in detecting pulmonary infections in ILD [10] For patients with covid-19 infection, HBP is signi cantly elevated, and its levels are negatively correlated with oxygen saturation, creatinine and lactate levels. Moreover, HBP has been found to be an independent risk factor for death within 28 days [21].…”
Section: Discussionmentioning
confidence: 99%
“…HBP has been shown to be able to directly kill both Gram-positive and Gram-negative bacteria, and further enhance bacterial clearance by attracting macrophages, lymphocytes, and even more neutrophils to the site of infection [8]. Hence, HBP has been suggested to be a novel and valuable biomarker in sepsis and interstitial lung disease complicated by infection [9,10].…”
Section: Introductionmentioning
confidence: 99%